Political advocacy in pharmacy: challenges and opportunities - Apollonio DE (Dove Medical Press, 2014)
Dorie E Apollonio Department of Clinical Pharmacy, University of California, San Francisco, San Francisco, CA, USA Abstract: Many pharmacists have expressed a desire to become more involved in patient care, in part by being compensated for patient counseling, as well as by providing services traditionally offered by physicians and nurse practitioners. Recent efforts to develop collaborative care models, as well as major restructurings of US health insurance coverage, provide a unique opportunity for pharmacists to become recognized as independent health care providers and be reimbursed as primary care providers. Achieving that goal would require addressing advocacy challenges familiar to other health care professionals who have achieved provider status under existing reimbursement rules. Historically, political advocacy has not been a major part of pharmacy practice, or even viewed as necessary. However, pharmacists would be more politically effective with a single organization to speak for them as a profession, and with further education in advocacy. Keywords: primary care provider, advocacy, pharmacy practice, patient care, reimbursement